Are there techno-scientific projects in Mexico? - VEGA-GONZÁLEZ, LUIS ROBERTO (Archives of Business Research, 2015)
The techno-scientific projects emerged during the 40’s decade, and were consolidated in the United States of America pending the last decades of last century. This work’s objective is to provide elements to understand how the techno-science systems of the developed countries function, to later visualize if there are similar projects in Mexico. The methodology used was the documents revision and a brief historical analysis of science, technology and engineering evolution to understand the essence of the disciplines that provided knowledge for the emergence of the techno-science. Furthermore, the relationship among science, technology, society and the techno-scientific projects is discussed from an axiological perspective. The results are that techno-science is not just the conjunction of the science and technology words, but a deeper issue that has to do with the action and the way in which big projects of research, development and innovation (R&D+i) should be performed. These projects must have national scope and high social impact. The conclusion is that while it is true that the techno-scientific projects are well consolidated in the United States of America and in some developed countries, this does not occur in developing countries and therefore the incipient techno-scientific work teams face serious difficulties to develop innovation projects within the Mexican science and technology system in the different productive and service sectors of the economy.